Designing multi-objective whole landscape scenarios at the catchment scale - Adrian Southern (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2010)
A critical task facing humanity is the creation of a shared vision for a sustainable society. This brings the question of the future to the strategic forefront of decision making, where decisions often need to be formulated in the face of profound uncertainty and complexity. In such circumstances scenario analysis and planning can offer a structured way of dealing with the many uncertainties that lie ahead. However, the fusion of quantitative and qualitative data in scenario design, which combines computational modelling with societal values, is still in its infancy presenting significant methodological challenges. This paper reports the findings of a participatory scenario development process using the 115 km2 River Glaven catchment in North Norfolk, England as a case study. A range of data sources were integrated to model soil erosion, ecological connectivity, land use change and agricultural economics. In addition a wide range of stakeholders were engaged with to design two landscape scenarios for the catchment in 2020. One scenario was driven by agricultural production and world trade, the other by the enhanced protection of ecosystem services and multi-objective land use. Based on the results of this case study we present recommendations for implementing integrated participatory and model-based scenario design processes for both practitioners and researchers.
Keywords: 330; scenario design; integrated modelling; ecosystem services; land use; catchment management; Umweltqualität; Nachhaltigkeit; Entscheidung bei Unsicherheit; Großbritannien